(untitled) (Nativa, 2023)
ABSTRACT: Pterocarpus angolensis DC and Bobgunnia madagascariensis (Desv.) J. H. Kirkbr. & Wiersema are two hardwood species found in Miombo woodland. Crown size, being closely related to the photosynthetic capacity of a tree, is an important parameter in studies of the growth of individual trees. In this sense, the present study aimed to study the morphometric relationships of P. angolensis and B. madagascariensis as a resource to describe the morphometric features of these species. Data were sampled in 60 rectangular plots of 20 x 50 m, systematically distributed within the forest. In each plot, the diameter at breast height (DBH), height (h), crown insertion point (cih) and four crown radii of all trees with DBH ≥ 10 cm were measured. Results indicated that crown diameter and crown length of P. angolensis grow as DBH and height increase, the larger the crown, the greater the trees dimensions; as for B. madagascariensis, crown features have shown low correlation when considering DBH. It was concluded that crown features influence on tree growth and are important measures of description and planning of silvicultural activities to be performed in natural forests. The results are of interest to forest managers since they make decisions about silvicultural operations. Keywords: crown dimensions; prediction models; umbila; pau-ferro; forest management. Morfometria da copa para duas espécies madeireiras comerciais da floresta de Miombo em Moçambique RESUMO: Pterocarpus angolensis DC e Bobgunnia madagascariensis (Desv.) J. H. Kirkbr. & Wiersema são duas espécies de madeira de lei encontradas na floresta de Miombo. O tamanho da copa, está intimamente relacionado à capacidade fotossintética de uma árvore, e é um parâmetro importante nos estudos do crescimento de árvores individuais. Nesse sentido, o presente estudo teve como objetivo estudar as relações morfométricas de P. angolensis e B. madagascariensis como recurso para descrever as características morfométricas dessas espécies. Os dados foram obtidos em 60 parcelas retangulares de 20 x 50 m, distribuídas sistematicamente na floresta. Em cada parcela, foram medidos o diâmetro à altura do peito (DAP), altura (h), altura de inserção da copa (hic) e quatro raios da copa de todas as árvores com DAP ≥ 10 cm. Os resultados indicaram que o diâmetro e o comprimento da copa de P. angolensis crescem com o aumento do DAP e da altura; quanto maior a copa, maior dimensão das árvores, enquanto que para B. madagascariensis, as características da copa mostraram baixa correlação ao considerar o DAP. Concluiu-se que as características da copa influenciaram no crescimento das árvores e são importantes medidas de descrição e planejamento das atividades silviculturais a serem realizadas na floresta. Estes resultados são de interesse dos manejadores florestais, pois são eles que tomam decisões sobre as operações silviculturais. Palavras-chave: dimensões da copa; modelos preditivos; umbila; pau-ferro; manejo florestal.